Using Digital 3D Scanning to Create “Artifictions” of the Passenger Pigeon and Harelip Sucker, Two Extinct Species in Eastern North America: The Future Examines the Past - Manzano, Bruce L.; Means, Bernard K.; Begley, Christopher T.; Zechini, Mariana (Ethnobiology Letters, 2015)
The Virtual Curation Laboratory at Virginia Commonwealth University created 3D representations of digital morphological models, termed “artifictions,” of several bone elements from two extinct animals, the passenger pigeon (Ectopistes migratorius Linnaeus Columbidae) and the harelip sucker (Moxostoma lacerum Jordan and Brayton Catostomidae). Procuring recent comparative reference skeletons these species is extremely difficult. The creation of artifictions, 3D printed replicas of skeletal remains, aims to help researchers become familiar with the bones of harelip sucker and passenger pigeon to facilitate morphological identification of remains of these species within archaeological assemblages. Here, we discuss the two species, the techniques used to create digital topological models of individual skeletal elements, and the obstacles encountered regarding 3D printed artifictions in zooarchaeology.